2007
DOI: 10.1677/jme-07-0027
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference of androgen actions on skeletal muscle transcriptome

Abstract: Sarcopenia is related to metabolic syndrome in postmenopausal women. Hormone replacement therapies with androgens improve muscle functions by molecular mechanisms that are still unknown, at least partly because the skeletal muscle transcriptome has been less characterized in females. We performed the serial analysis of gene expression method in six experimental groups, intact (male and female), ovariectomy (OVX), OVXCdihydrotestosterone (DHT) injection 1, 3, or 24 h before kill in mice. The 438 transcript spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…1), which could indicate a greater proportion of oxidative fiber types. This pattern is confirmed by the significantly decreased Troponin T3 fast transcription observed in female C57/BL6 murine gastrocnemius muscle by Yoshioka et al [5]. A greater proportion of oxidative fibers is consistent with the increased expression found for myoglobin in our female mice.…”
Section: Non-metabolic Proteinssupporting
confidence: 91%
See 3 more Smart Citations
“…1), which could indicate a greater proportion of oxidative fiber types. This pattern is confirmed by the significantly decreased Troponin T3 fast transcription observed in female C57/BL6 murine gastrocnemius muscle by Yoshioka et al [5]. A greater proportion of oxidative fibers is consistent with the increased expression found for myoglobin in our female mice.…”
Section: Non-metabolic Proteinssupporting
confidence: 91%
“…This trend is similar to the human vastus lateralis mRNA assay performed by Roth et al [6] in which they found more than three fourths of transcripts up-regulated in males, though the specific proteins are not similar to those presented here. Of interest is that three protein fragments identified here were found to have increased transcription by Yoshioka et al (ATP synthase, H+ transporting mitochondrial F1 complex, beta subunit; Malate dehydrogenase 2, NAD [mitochondrial]; Aconitase 2, mitochondrial) [5], despite insignificant expression differences of the full-length protein between genders. This could indicate an increased turnover rate of these proteins in females when compared to males.…”
Section: Quantificationmentioning
confidence: 56%
See 2 more Smart Citations
“…In the current study LMA increased in rams, which was expected. This increase may be due to muscle hypertrophy, stimulation by testosterone treatment in later postnatal periods, direct or indirect satellite cell proliferation or muscle protein synthesis (Yoshioka, Boivin, Bolduc, & St-Amand, 2007). According to Haddad, Husein, and Swedan (2006), there was no effect of castration in lambs for HCW, CCW, dressing percentage, or LMA.…”
Section: Resultsmentioning
confidence: 97%